Changes in flower development, chlorophyll mutation and alteration in plant morphology of Curcuma alismatifolia by gamma irradiation - Abdullah, Thohirah Lee; Endan, Johari; Basiran, Mohd Nazir (Science Publications, 2009)
Problem statement: Curcuma alismatifolia Gagnep., commonly known as 'Thai tulip' or pathumma is a member of the family Zingiberaceae. This herbaceous perennial which can be grown from rhizomes have a great potential for use as a cut flower, flowering potted plant and as a garden plant for tropical landscaping. Unlike other bulbous floral crops, research on C. alismatifolia using gamma irradiation has been a least subject of investigation. Approach: Presently, the use of induced mutation in plant improvement had become a proven way that can generate new sources of genetic variations in creating new varieties. This additional tool is important in plant improvement, which was a valuable approach to plant breeding in the world of ornamental industry. A study on the effects of gamma irradiation on mutagenesis of Curcuma alismatifolia was conducted to determine the optimal dose for radiosensitivity test (LD50) of the plants and also to determine the effects of induced mutation on the species. This study was carried out at the Malaysian Nuclear Agency (Nuclear Malaysia), Bangi. Ten levels (dose rate) of gamma irradiation were used in this study. Data collection for days of shoot emergence, plants height, number of leaves and shoots, days to bloom, height of flowering stalks, inflorescence size and the days to anthesis (post-production longevity) were taken. Results: Results obtained showed that the highest survival rate was 67% obtained from the non-irradiated rhizomes (0 Gy). Fifty percent when were treated with 10 Gy and 63% survival rate when treated at 20 Gy. Mean survival rate fell sharply from 63% at 20 Gy to 7% at 30 Gy. This decreasing trend was followed by 2% survival at 40 Gy. Results indicated that the radiosensitivity test (LD50) for the Curcuma alismatifolia was approximately at 25 Gy. Conclusion: Gamma irradiation had exerted various effects on growth of C. alismatifolia, including the survival rate of rhizomes, extension of days to shoot emergence, plant height, leaves and shoots number as well as modifications in plant morphology and flower development.